Exploration of Religious Activities of the Taklim Assembly as a Learning Resource on Social Studies - Ersis Warmansyah Abbas; Mutiani Mutiani; Disman Disman; Erlina Wiyanarti (Social Studies Education Department, Faculty of Teacher Training and Education, Universitas Lambung Mangkurat, 2022)
The taklim assembly is one of the religious activities carried out in the community. The existence of the taklim assembly is essential in instilling religious values ​​into the community during the moral decline that is currently an issue. In addition, with the taklim assembly, the community can also interact with one another. Therefore, this religious activity of the taklim assembly can also be used as a learning resource in social studies, which aims to make it easier for educators to provide contextual examples to students. So this study describes the religious activities of the taklim assembly as a source of social studies learning. This study uses a qualitative approach with descriptive methods and data collection through observation, interviews, and documentation. Data analysis techniques include data reduction, presentation, member checks, and triangulation. The results of the study describe that the religious activities of the taklim assembly can be used as a learning resource on social studies because, in this case, the environment is also a necessity in obtaining information in knowing something, so that the environment can be used as a learning resource on social studies for students.